Global prospects to deliver safe drinking water services for 100 million rural people by 2030 - Nilsson, K; Hope, R; McNicholl, D; Nowicki, S; Charles, K (University of Oxford and RWSN, 2021)
The climate crisis and global pandemic have accelerated the urgency of providing safe drinking water services around the world. Global progress to safe drinking water is off-track with uncertain and limited data on the extent and performance of rural water service providers to inform policy and investment decisions. This report documents a global diagnostic survey to evaluate the status and prospects of rural water service providers from 68 countries. The service providers describe providing drinking water services to a population of around 15 million people through over 3 million waterpoints.